BCL6 promotes the progression of high-grade serous ovarian cancer cells by inhibiting PLAAT4 - Wan, An; Zhao, Wei-Dong; Chen, Gang; Peng, Cheng; Tao, Jin-Hui (Frontiers in Pharmacology, 2025)
BackgroundB-cell lymphoma 6 (BCL6) is increasingly recognized as a driver of cancer progression; however, the precise molecular mechanisms by which BCL6 facilitates high-grade serous ovarian cancer (HGSOC) progression remain incompletely understood.MethodsIn this study, immunohistochemical (IHC) staining was used to evaluate the expression of BCL6 and PLAAT4 in HGSOC tissues and normal tissues. Cleavage under targets and tagmentation (CUT&Tag) was combined with RNA sequencing (RNA-seq) analyses to screen and identify the downstream regulatory mechanisms of BCL6. Wound healing assays, plate cloning, EdU, and transwell assays were used to analyze cell proliferation and invasion. The expression of PI3K-AKT, EMT, and proliferation markers were analyzed by immunohistochemistry in vivo or by Western blot in vitro. In vivo, we established a subcutaneous transplantation tumor model and abdominal metastasis model in nude mice to verify the role of BCL6 and PLAAT4 in HGSOC progression.ResultsClinical analyses revealed that BCL6 expression is significantly elevated in high-grade serous ovarian cancer (HGSOC) tissues compared with that in normal tissues, whereas PLAAT4 expression is reduced. Moreover, high BCL6 and low PLAAT4 expression are associated with poor prognosis in patients with HGSOC. Biological function tests showed that BCL6 contributes to tumor cell proliferation, invasion, and migration, and plays an important role in the progression of HGSOC in vivo. Mechanistically, our investigation revealed that BCL6 promotes HGSOC progression by downregulating PLAAT4, thereby influencing the activation of the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway.ConclusionCollectively, these findings elucidate the pivotal role of the BCL6-PLAAT4-AKT axis in HGSOC progression, establishing a molecular framework for targeting this pathway as a potential therapeutic strategy against HGSOC.